Effect of self-monitoring and medication self-titration on systolic blood pressure in hypertensive patients at high risk of cardiovascular disease: the TASMIN-SR randomized clinical trial. - McManus, R; Mant, J; Haque, MS; Bray, E; Bryan, S; Greenfield, S; Jones, M; Jowett, S; Little, P; Penaloza, C; Schwartz, C; Shackleford, H; et al. (American Medical Association, 2014)
IMPORTANCE: Self-monitoring of blood pressure with self-titration of antihypertensives (self-management) results in lower blood pressure in patients with hypertension, but there are no data about patients in high-risk groups. OBJECTIVE: To determine the effect of self-monitoring with self-titration of antihypertensive medication compared with usual care on systolic blood pressure among patients with cardiovascular disease, diabetes, or chronic kidney disease. DESIGN, SETTING, AND PATIENTS: A primary care, unblinded, randomized clinical trial involving 552 patients who were aged at least 35 years with a history of stroke, coronary heart disease, diabetes, or chronic kidney disease and with baseline blood pressure of at least 130/80 mm Hg being treated at 59 UK primary care practices was conducted between March 2011 and January 2013. INTERVENTIONS: Self-monitoring of blood pressure combined with an individualized self-titration algorithm. During the study period, the office visit blood pressure measurement target was 130/80 mm Hg and the home measurement target was 120/75 mm Hg. Control patients received usual care consisting of seeing their health care clinician for routine blood pressure measurement and adjustment of medication if necessary. MAIN OUTCOMES AND MEASURES: The primary outcome was the difference in systolic blood pressure between intervention and control groups at the 12-month office visit. RESULTS: Primary outcome data were available from 450 patients (81%). The mean baseline blood pressure was 143.1/80.5 mm Hg in the intervention group and 143.6/79.5 mm Hg in the control group. After 12 months, the mean blood pressure had decreased to 128.2/73.8 mm Hg in the intervention group and to 137.8/76.3 mm Hg in the control group, a difference of 9.2 mm Hg (95% CI, 5.7-12.7) in systolic and 3.4 mm Hg (95% CI, 1.8-5.0) in diastolic blood pressure following correction for baseline blood pressure. Multiple imputation for missing values gave similar results: the mean baseline was 143.5/80.2 mm Hg in the intervention group vs 144.2/79.9 mm Hg in the control group, and at 12 months, the mean was 128.6/73.6 mm Hg in the intervention group vs 138.2/76.4 mm Hg in the control group, with a difference of 8.8 mm Hg (95% CI, 4.9-12.7) for systolic and 3.1 mm Hg (95% CI, 0.7-5.5) for diastolic blood pressure between groups. These results were comparable in all subgroups, without excessive adverse events. CONCLUSIONS AND RELEVANCE: Among patients with hypertension at high risk of cardiovascular disease, self-monitoring with self-titration of antihypertensive medication compared with usual care resulted in lower systolic blood pressure at 12 months. TRIAL REGISTRATION: isrctn.org Identifier: ISRCTN87171227.